To a Question on Classification of Factors of Formation of an Innovative Susceptibility of Region - ВладимироваОльга Николаевна; ДягельОксана Юрьевна (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2011)
Authors: Olga Nikolaevna Vladimirova - National Research University "Higher School of Economics." Oksana Yurevna Dyagel - National Research University "Higher School of Economics." In article ordering and classification of factors of an innovative susceptibility of region with use of structure of the signs having different properties (influence degree, character and level of influence, structure of innovative activity, etc.) is spent. It allows defining possible directions of rendering of administrative influence on readiness of region for realization of innovations.